ANALISIS TINGKAT KEMAMPUAN MASYARAKAT DALAM MERAWAT JENASAH SECARA ISLAMI DI KELURAHAN PEDALANGAN KECAMATAN BANYUMANIK SEMARANG - Sayoto Makarim; Daryono Daryono; Dini Anggraheni (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
The Purpose of this study is to sosialize the understanding of treating a dead body in Islamic ways in Pedalangan Village, Banyumanik Sub District, Semarang. The method used in this study is descriptive qualitative through pretest and postest as the tools to analyze and solve the problems. This study is able to provide solutions to various deficiencies in understanding how to take care of dead body in Islamic way with 3.8%-53.9% incremental understanding. Key words: society, take care of dead body, increase the understanding